Effects of latanoprost on the expression of TGF-Î²1 and Wnt / Î²-catenin signaling pathway in the choroid of form-deprivation myopia rats - Suo, Nan-cuo; Lei, Chun-ling; Zhang, Yan-chun; Li, Xin-zhang; Li, Feng-zhi; Gong, Ke (Cellular and Molecular Biology, 2020)
In this study, we investigated the effect of latanoprost on the expression of TGF- Î²1 and Wnt / Î² - Catenin signal pathway in the choroid of form-deprivation myopia model rats. Forty rats were randomly divided into two groups: the control group and the FDM model group. Each group had 20 rats. The FDM model group was established by feeding latanoprost daily for 28 days. 15 rats in each group were used to measure the length of the ocular axis and the level of TGF-Î²1 in choroidal tissue; the remaining 5 rats in each group were used for choroidal fibroblast culture. After modeling, the rats were killed, the length of the ocular axis was measured with a vernier caliper, and the level of TGF - Î²1 protein and mRNA in the choroidal tissue of each group were measured with RT-PCR method. Results showed that compared with the control group, there was a significant difference in the axial length of the FDM model group (P< 0.05). There was a significant difference in the expression of TGF- Î²1 protein and mRNA between the two groups (P<0.05). The cultured cells were identified as choroidal fibroblasts by immunocytochemistry. There was no significant difference (P>0.05) in the comparison of GSK3 Î² protein in choroidal fibroblasts of rats in each group. TGF-Î² 1 and APC protein in FDM group were significantly lower than those in the control group (P<0.05), while dcl3, p21-gsk3 Î² and Î² - Catenin proteins were significantly higher (P<0.05), and there was no significant difference (P>0.05) in the ratio of various indexes protein in FDM + ddk1 group and the comparison of TGF - Î²1 and APC protein in FDM + ddk1 group and FDM group The expression of dcl3, p21-gsk3 Î² and Î² - Catenin decreased significantly (P<0.05). There was no significant difference in the expression of GSK3 Î² mRNA in the choroidal fibroblasts of each group (P>0.05). The expression of TGF - Î² 1 and APC mRNA in FDM group was significantly lower than that in the control group (P<0.05), while the expression of dcl3, p21-gsk3 Î² and Î²-catenin mRNA in FDM + ddk1 group was significantly higher than that in the control group (P<0.05) >In FDM + ddk1 group, TGF-Î² 1 and APC mRNA were significantly lower than those in FDM group (P<0.05), while dcl3, p21-gsk3 Î² and Î²-Catenin mRNA were significantly higher (P<0.05).